Analysis of GNSS-R Code-Level Altimetry Using QZSS C/A, L1C, and BDS B1C Signals and Their Combinations in a Coastal Experiment - Nazi Wang; Kaifei He; Fan Gao; Ti Chu; Jinhua Hou; Tianhe Xu (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2023)
The fully completed Quasi-Zenith Satellite System (QZSS) and BeiDou Navigation Satellite System (BDS-3) can provide higher precision code observations owing to their advanced signal modulation. However, the performance of Global Navigation Satellite System-Reflectometry (GNSS-R) code-level altimetry using the new codes is rarely be tested. In this study, interoperable signals with the frequency of 1575.42 MHz, i.e., L1C/A and L1C from QZSS and B1C from BDS, were tested for GNSS-R altimetry simultaneously for the first time. Moreover, a joint weighted GNSS-R altimetry method is proposed to improve retrieval precision based on combinations of the path delays obtained from different signals. To investigate the performance of the signals and their combinations, a ground-based GNSS-R altimetry experiment was conducted and raw intermediate-frequency data were collected over several hours. These data were processed using a software-defined receiver to compute the path delay between the direct and reflected signals. Solutions were derived separately for each code and their combinations. Through comparison with reflector heights obtained from an in situ 26 GHz radar gauge, results showed that the performance of GNSS-R altimetry based on binary offset carrier modulation signals was better than that from binary phase-shift keying. Moreover, results from the joint weighted GNSS-R altimetry method showed further improvement in altimetry precision.